2016
DOI: 10.1016/j.mce.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-1 expression is increased in aggressive thyroid cancer and favors the migration and invasion of cancer cells

Abstract: In this study we analyzed the expression levels of markers of epithelial-to-mesenchymal transition (EMT) in several papillary thyroid carcinomas (PTCs) and the relation with tumor genotypes and clinicopathological characteristics. The role of fibronectin-1 (FN1) was investigated by analyzing the effects of FN1 silencing in two human thyroid cancer cell lines. Most of EMT markers were significantly over-expressed in a group of 36 PTCs. In particular, FN1 mRNA levels were higher in tumor vs non-tumor tissue (117… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 55 publications
1
100
0
3
Order By: Relevance
“…There are functional genes modulating EMT, resulting in tumor progression 32. Fibronectin 1 is one of the EMT regulators that was found to be upregulated in aggressive TC 11. In our study, the role of fibronectin 1 was investigated in PTC cell lines.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There are functional genes modulating EMT, resulting in tumor progression 32. Fibronectin 1 is one of the EMT regulators that was found to be upregulated in aggressive TC 11. In our study, the role of fibronectin 1 was investigated in PTC cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…Serum fibronectin could be a promising biomarker for detecting breast cancer at an early stage 10. Another recent study indicated that fibronectin 1 was upregulated in aggressive TC 11. However, the biological function of fibronectin 1 in PTC has never been reported, and the clinical significance of fibronectin 1 in LNM of papillary TC is still unclear 12,13…”
Section: Introductionmentioning
confidence: 99%
“…The EMT is important for tumor cells to acquire migratory and invasive properties [28, 29], and was recently implicated in several types of invasive human malignancies [3033], including CRC [34]. Hence, EMT and its markers, including CDH1, are useful diagnostic biomarkers or therapeutic targets in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINE1 may also contribute to tumor aggressiveness by promoting tumor angiogenesis 26,27. FN1 has long been considered as an epithelial–mesenchymal transition (EMT) marker and is associated with angiogenesis and metastasis 28,29. Genes with lower AUC may significantly complement the model, however, we are more inclined to select biomarkers which are up-regulated in recurrent tumors compared to non-recurrent tumors such as THBS1, SERPINEE1, and FN1.…”
Section: Discussionmentioning
confidence: 99%